Stepwise project: Sorption-enhanced water-gas shift technology to reduce carbon footprint in the iron and steel industry: - Dijk, H.A.J. van; Cobden, P.D.; Lukashuk, L.; Water, L. van de; Lundqvist, M.; Manzolini, G.; Cormos, C.C.; Dijk, C. van; Mancuso, L.; Johns, J.; Bellqvist, D. (Johnson Matthey Public Limited Company, 2018)
Industrial processes contribute significantly to global carbon dioxide emissions, with iron and steel manufacturing alone responsible for 6% of the total figure. The STEPWISE project, funded through the European Horizon 2020 (H2020) Low Carbon Energy (LCE) programme under grant agreement number 640769, is looking at reducing CO2 emissions in the iron and steel making industries. At the heart of this project is the ECN technology called sorption-enhanced water-gas shift (SEWGS), which is a solid sorption technology for CO2 capture from fuel gases such as blast furnace gas (BFG). This technology combines water-gas shift (WGS) in the WGS section with CO2/H2 separation steps in the SEWGS section. Scaling up of the SEWGS technology for CO2 capture from BFG and demonstrating it in an industrially relevant environment are the key objectives of the STEPWISE project, which are achieved by international collaboration between the project partners towards design, construction and operation of a pilot plant at Swerea Mefos, Luleå, Sweden, next to the SSAB steel manufacturing site. © 2018 Johnson Matthey.